НАЦІОНАЛЬНА ВИШИВКА, ЯК ЗАСІБ РОЗВИТКУ ЕСТЕТИЧНИХ СМАКІВ УЧНІВ (Педагогіка вищої та середньої школи, 2008)
The necessity of development of aesthetical taste and sense of beautiful is basic direction of labour éducation. Ukrainian folk embroidery is one of ponderable composites by which the teacher of attendant labour can attain the most effective forming of aesthetical taste.